Analisis Hasil Belajar Psikologi Mahasiswa ditinjau dari Perbedaan Kepribadian - Eman Sulaeman (Ta'lim: The Islamic Religious Educational Journal, 2024)
Inclusive education represents an educational paradigm that places all learners—including those with special needs—within a single learning system that is equitable, non-discriminatory, and adaptive. In the context of Islamic education, the concept of inclusion possesses a strong theological foundation, both in the Qur’an and the Hadith, which emphasize the importance of justice, respect for diversity, and equal learning opportunities for every individual. This study aims to analyze the paradigm of inclusive education from the perspective of Islamic education through a literature review of classical and contemporary sources. The research employs a library research methodology with a content-analysis approach, focusing on theories of inclusive education, Islamic teachings on diversity, the value of justice, the concept of *fitrah*, and the implementation of inclusive practices in Islamic educational institutions in Indonesia. The findings indicate that the inclusive paradigm aligns with Islamic principles concerning human dignity, the mandate to educate without discrimination, and the obligation to strengthen learning environments that are welcoming, adaptive, and humane. This article affirms that inclusive education is not only compatible with Islamic education but also constitutes an integral part of its objectives, which position every learner as a unique individual who must be guided toward the perfection of their fitrah.